SYNTHESIS AND PHYSICOCHEMICAL PROPERTIES OF ACETYLENE AMINO ALCOHOLS - А. K. Mamyrbekova; M. K. Kassymova; A. B. Bayeshov; А. K. Mamyrbekova; A. D. Mamitova; O. N. Chechina (Scientific Journal of Pedagogy and Economics, 2019)
The article is given an overview of publications devoted to the synthesis of acetylenic amino alcohols and the possibility of obtaining on their basis of microbiologically active compounds by interaction with phenyl isocyanate and phenyl isothiocyanate. Acetylene amino alcohols having not only biological activity, but also other valuable properties, are also the basis for obtaining their derivatives. The yield of derivatives of acetylene amino alcohols by Manich reaction was 66-73%. Implementation of the reaction at high temperature leads to the passing of side processes, in particular, the decomposition of acetylene alcohols, resin formation and others. Absorption spectra corresponding to functional groups and bonds of acetylene amino alcohols are observed on IR spectra. Physical and chemical characteristics of acetylene amino alcohols were determined: boiling point, chromatographic characteristics of Rf substance, elemental composition of carbon, hydrogen, nitrogen (mass.) and gross formulas.